DISKURSUS PENGAMALAN BERQURBAN MENURUT LDII DAN AL WASHLIYAH; BERQURBAN SECARA BERJAMA’AH (PATUNGAN) - Wardi, Syah; Waldi, Irfa (UIN Sumatera Utara, 2021)
Abstract: This article discusses the implementation of qurban in congregation (joint venture) according to two mass organizations that were born and raised in the midst of the joints of this country's life. In particular, this article will raise issues that often occur when carrying out qurbani worship in the community, for this reason this study will focus on the issue of qurban in congregation (joint venture), what is meant by joint venture? what is the urgency of qurban in congregation in qurban practice? And where is the point of contact between LDII and Al Washliyah regarding qurban in congregation (joint venture). This study is case research and field research (Case Study and Field Research), so this research focuses on a case in an incentive and detailed manner regarding the background of the situation at issue. Keywords: Qurban, LDII, Al Washliyah